Influence of Teacher Planning on Students’ Academic Performance in Kwale County, Kenya - Mboko, Caleb Were; Kithinji, Winfred; Mutunga, Stephen Laititi (International Journal of Professional Practice, 2023)
This research examined the influence of teacher planning using professional documents on teachers’ time management and secondary school students’ academic performance in Kwale County, Kenya. Pareto theory was used in the study. The target population comprised of 98 principals, 960 teachers and 6,540 form four students from public secondary schools in Kwale County. Krejcie and Morgan's formula was used to calculate the sample size, and a sample of 274 instructors, 364 form four students, and 29 principals was established. Utilizing a standardized questionnaire, data were gathered. Quantitative data was analyzed descriptively and presented as percentages and regression analysis. Validity of the research instrument was established after being examined for logical content by university supervisors who were specialists in the area. Internal reliability was estimated through Cronbach’s alpha in which a reliability coefficient of α= .83 was established. The study established a statistical significance p = 0.000 (<0.05, α=0.05), of teacher planning on students’ academic performance. Regression results indicated that teacher planning using professional documents accounted for 36.3% (R2=.363) of students’ academic performance. The study found that proper planning was essential for a successful teaching and learning process. This paper makes the case for the value of lesson planning and schemes of work in instruction.